Weighted LabPQR Interim Connection Space Based on Human Color Vision for Spectral Color Reproduction - Wu, Guangyuan; Liu, Zhen; Yang, Shengwei; Zhu, Ming; Liu, Pan (Journal of Spectroscopy, 2014)
A weighted LabPQR interim connection space, based on human color vision, is proposed for retaining more visual color information. A new weight function proposed in our paper is connected with color-matching function and then further weighted the PQR dimensions of LabPQR compared with the other two weight functions and nonweight function. The results indicated that weighting obviously improved the colorimetric representing accuracy and robustness compared with nonweighting, and the new weight function outperformed the other two weight functions. The weighted LabPQR of the new weight function is most suitable for spectral color reproduction.